2011
DOI: 10.1007/s00213-011-2453-7
|View full text |Cite
|
Sign up to set email alerts
|

Developmental differences in ethanol-induced sensitization using postweanling, adolescent, and adult Swiss mice

Abstract: Young mice develop very strong ethanol sensitization at doses that mimic binge drinking in humans. These results might explain why early ethanol drinking during adolescence is related to a higher prevalence of subsequent alcohol disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 68 publications
2
12
0
Order By: Relevance
“…Our results indicate that animals that achieved the highest levels of sensitization were not the same as those that developed the highest tolerance to the depressant effect of EtOH. This study is in line with recent reports by Quoilin and colleagues who showed in outbred mice that adolescents require high ethanol doses to develop EIBS [38], and do not display any chronic tolerance to the sedative effect of EtOH using the same schedule of EtOH administrations [39]. They concluded that the development of EIBS in adolescent mice is not related to tolerance to the sedative effect of EtOH.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results indicate that animals that achieved the highest levels of sensitization were not the same as those that developed the highest tolerance to the depressant effect of EtOH. This study is in line with recent reports by Quoilin and colleagues who showed in outbred mice that adolescents require high ethanol doses to develop EIBS [38], and do not display any chronic tolerance to the sedative effect of EtOH using the same schedule of EtOH administrations [39]. They concluded that the development of EIBS in adolescent mice is not related to tolerance to the sedative effect of EtOH.…”
Section: Discussionsupporting
confidence: 92%
“…Mice were housed in groups of 10 in clear plastic cages (24 × 42 ×15 cm) and kept in a temperature (21 ± 0.5°C) and humidity-controlled (55 ± 10%) environment under an established photoperiod (07.00 -19.00 hours) with free access to food (Mouse and Rats, Maintenance, Extrudate; Provimi Kliba, Kaiseraugst, Switzerland) and tap water. In the present study, we used female mice in continuity with our previous work [13,[35][36][37][38][39][40][41] and also to keep consistency with the most relevant reports supporting our working hypothesis [37,39]. The number of animals was kept to a minimum, and all efforts were made to limit stress and to avoid animal suffering.…”
Section: Subjectsmentioning
confidence: 98%
See 1 more Smart Citation
“…intubation, which favored the expression of stimulant effects of ethanol. These results are consistent with studies conducted in Swiss mice (Quoilin, Didone, Tirelli, & Quertemont, 2012) and Sprague-Dawley rats (Acevedo et al, 2013), which considered the motor stimulant effects of ethanol as a proxy for ethanol's positive reinforcing effects.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, when examining ethanol-induced locomotor sensitization in mice, adolescents did not exhibit a context-dependent sensitization that was evident in adults (Faria et al, 2008). Moreover, in another study, adolescents required higher doses than adults in order to exhibit sensitization to ethanol, although once adolescents were given sufficiently high doses to express sensitization, they expressed greater sensitization than adults (Quoilin et al, 2012). Interestingly, whereas adolescents did not show context-dependent sensitization in the Faria et al (2008) study, they did express sensitization of the locomotor stimulant response when ethanol was given in the home cage rather than being paired with the test context—data which suggest that adolescents may find it difficult to show increased incentive salience to reward-predictive cues.…”
Section: Adolescent Sensitivity To Rewardsmentioning
confidence: 99%